2019
DOI: 10.1186/s40635-019-0285-7
|View full text |Cite
|
Sign up to set email alerts
|

Four hours of veno-venous extracorporeal membrane oxygenation using bi-caval cannulation affects kidney function and induces moderate lung damage in a mouse model

Abstract: Background: Improvement of single site cannulation for extracorporeal membrane oxygenation (ECMO) therapy is pivotal for reduction of patient morbidity and mortality in respiratory failure. To further improve the cardiopulmonary outcomes and reduce end organ damage, we established a murine model for single site cannulation with a double lumen cannula. Results: We created a hemodynamically stable double lumen cannula and successfully implanted it through the jugular vein into the upper and lower vena cava. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…A possible explanation can be that the oxygen tension is lowest in the renal outer medulla which makes this region most vulnerable to ischemic injury [ 23 ]. In contrast, a previous study showed that vv ECMO in mice for 4 h caused a slight increase in neutrophil infiltration in the glomeruli and tubule-interstitial space [ 24 ]. However, in our study no major renal neutrophil infiltration was observed after ECMO treatment for 2 h which might be explained by the shorter duration of ECMO treatment.…”
Section: Discussionmentioning
confidence: 80%
“…A possible explanation can be that the oxygen tension is lowest in the renal outer medulla which makes this region most vulnerable to ischemic injury [ 23 ]. In contrast, a previous study showed that vv ECMO in mice for 4 h caused a slight increase in neutrophil infiltration in the glomeruli and tubule-interstitial space [ 24 ]. However, in our study no major renal neutrophil infiltration was observed after ECMO treatment for 2 h which might be explained by the shorter duration of ECMO treatment.…”
Section: Discussionmentioning
confidence: 80%
“…Clinically, a VV-ECMO ow of 50-75% of the cardiac output is su cient for adequate oxygenation in ARDS patients on mechanical ventilation [11]. Unnecessary increases in VV-ECMO ow rate may cause hemolysis damage, and unnecessary recirculation of the main portion of venous blood between IVC and SVC [15]. Furthermore, we observed that increasing ECMO ow rate caused excessive negative pressure, which could cause air suction into intubation sites.…”
Section: Discussionmentioning
confidence: 83%
“…However, due to the existence of multiple potential entrances, including ECMO intubation, standard invasive catheters, and open chest wounds, etc., patients who receive ECMO are at a high risk of healthcare-associated infection, especially blood stream infection (BSI), central line associated bloodstream infections (CLABSI) (22,23). Moreover, the artificial surfaces of the ECMO circuit, such as the membrane oxygenator (MO), drainage cannula, the return cannula, could be the target of microbial adhesion and colonisation, thereby facilitating the development of ECMO-related bloodstream infection (24). After 7 years of retrospective cohort study found that 38 patients developed nosocomial infection after ECMO support, and the incidence of nosocomial infection was about 19.59% (38/194).…”
Section: Discussionmentioning
confidence: 99%